Fahrenheit 451: a marxist perspective on discourse, content, and form - Contreras Velasco, Daniela Andrea Aurora (Universidad de Santiago de Chile, 2021)
Integrantes: Daniela Andrea Aurora Contreras Velasco, Carolina Angélica Herrera Urrutia, Gonzalo Andrés Lagos Morales, José Antonio Monsalve Figueroa
Keywords: Bradbury, Ray, 1920-2012. Fahrenheit 451; Luchas sociales en literatura; Materialismo histórico